IMPLEMENTASI ETIKA PROFESIONAL GURU DALAM KOLABORASI BERBASIS PLATFORM DIGITAL UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN - Fahmi, Muhammad Nurul; Minatika, Naelum; Aenun Mutoharoh; muhlisin, Muhlisin; Mafaakhir, Abul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of teachers’ professional ethics and digital platform-based collaboration in improving the quality of learning in the digital era. The method used is a qualitative approach through a literature study and analysis of various scientific sources relevant to the research topic. The results show that the development of digital technology has provided significant opportunities for teachers to collaborate more broadly through various platforms such as Learning Management Systems (LMS), discussion forums, and online communication applications. The forms of collaboration include online discussions, team teaching, and sharing instructional materials among teachers. However, the implementation of professional ethics in digital collaboration still faces several challenges, such as low awareness of digital ethics, potential privacy violations, and the lack of professional language use in online communication. The application of teachers’ professional ethics plays an important role in maintaining the quality of interaction, building trust, and preventing conflicts in digital collaboration. Furthermore, ethical collaboration can enhance learning innovation and improve students’ learning outcomes. Therefore, strengthening teachers’ professional ethics and improving digital literacy are necessary to ensure that the use of technology in education can be carried out optimally and responsibly.